Investigation of Professional and Individual Characteristics Affecting Colleague Solidarity in Nurses - Hülya İncirkuş Küçük; Besti Üstün (Sağlık ve Hemşirelik Yönetimi Dergisi)
Aim: The study was conducted in a descriptive manner in order to examine the professional and individual characteristics that affect colleague solidarity in nurses. Method: The study was conducted with 210 nurses in a State Hospital. The data was obtained using a descriptive survey form and the Colleague Solidarity Scale in Nurses. Mann-Whitney U, Kruskal-Wallis and Dunun-Bonferroni tests were used to analyze the data. Results: The average scores of nurses from the Emotional Solidarity, Academic Solidarity, Negative Thoughts About Solidarity sub-dimensions and the total scale are respectively; They are 39.91 (SD=4.34), 38.24 (SD=4.78), 18.64 (SD=4.67) and 96.80 (SD=10.20). No difference was found in nurses' total HMDS scores according to age, marital status, child, family type, people they live with, sibling, father's education, and receiving the necessary support from colleagues. The level of collegiality is positively affected by being a woman, liking the profession, and satisfaction with the position. Men, those with low maternal education, those working in outpatient clinics, and graduates of health vocational high schools have more negative thoughts about solidarity. Those who live in a metropolitan city, love their profession, and are satisfied with their position have high levels of both academic and emotional solidarity. In addition, emotional solidarity of those who live with friends; The academic solidarity levels of branch nurses and association members were also found to be higher. Conclusion: The study showed that nurses' general collegiality score was high, and being a woman, being satisfied with their position and loving their profession positively affected the level of collegiality.